2018
DOI: 10.1038/s41409-018-0102-z
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of steroid and therapy-refractory acute graft-versus-host disease with a novel mesenchymal stromal cell product (MSC-FFM)

Abstract: The inability to generate mesenchymal stromal cells (MSCs) of consistent potency likely is responsible for inconsistent clinical outcomes of patients with aGvHD receiving MSC products. We developed a novel MSC manufacturing protocol characterized by high in vitro potency and near-identity of individual doses, referred to as “MSC-Frankfurt am Main (MSC-FFM)”. Herein, we report outcomes of the 69 patients who have received MSC-FFM. These were 51 children and 18 adults with refractory aGvHD grade II (4%), III (36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 28 publications
2
69
1
3
Order By: Relevance
“…The majority of clinical trials confirmed the safety of MSCs in steroid-refractory aGvHD in the pediatric as well as adult patient population with variable success rates [5, 22-27]. However, children showed a trend towards better CR compared with adults [25, 28].…”
Section: Mscs In the Treatment Of Agvhdmentioning
confidence: 97%
See 4 more Smart Citations
“…The majority of clinical trials confirmed the safety of MSCs in steroid-refractory aGvHD in the pediatric as well as adult patient population with variable success rates [5, 22-27]. However, children showed a trend towards better CR compared with adults [25, 28].…”
Section: Mscs In the Treatment Of Agvhdmentioning
confidence: 97%
“…This novel manufacturing protocol is characterized by high potency and near-identity of individual doses, termed MSC-Frankfurt am Main (MSC-FFM) [24]. Recently, Bader et al [5] reported outcomes of 69 adult and pediatric patients who received a total of 212 doses of MSC-FFM for therapy-refractory aGvHD in a routine clinical setting in 23 allogeneic transplant centers from 6 countries. The patients were either steroid-refractory (29%) or refractory to steroids plus 1–5 additional immunosuppressive agents (71%).…”
Section: Mscs In the Treatment Of Agvhdmentioning
confidence: 99%
See 3 more Smart Citations